Current role of interventional radiology in thyroid nodules - Taydas, Onur; Arik, Erbil; Sevinc, Omer Faruk; Kara, Ahmet Burak; Ozdemir, Mustafa; Cengiz, Hasret; Bayhan, Zulfu; Ozturk, Mehmet Halil (Frontiers in Endocrinology, 2024)
Thyroid nodules are a prevalent health issue in society. Interventional radiological methods are successfully applied for both the diagnosis and treatment of nodules. Diagnostically, a fineneedle aspiration biopsy and a core needle biopsy can be performed to ascertain the benign or malignant nature of a lesion. In recent years, imaging-guided percutaneous treatment methods have become popular in the treatment of thyroid nodules. Aspiration, ablation, and embolization are techniques employed in the treatment process. In this study, we aimed to discuss the current role of interventional radiology in the diagnosis and treatment of thyroid nodules, which occupy an important place in clinical practice.